Process intensification by model-based design of tailor-made reactors - Freund, Hannsjörg; Maußner, Johannes; Kaiser, Markus; Xie, Mingquan (Current Opinion in Chemical Engineering, 2019)
The most recent work in the field of model-based design of catalytic reactors with a special focus on the multi-level reactor design (MLRD) methodology is reviewed. The key idea of this method is to track a fluid element on its way through the — not yet specified — reactor and to optimize the reaction conditions along its way by providing the necessary material and energy fluxes. On the basis of these optimal flux profiles novel reactor concepts tailored to the needs of the reaction system can be derived and analyzed. Recent advances and extensions to handle the specifics of reaction systems with different complexity are presented. The MLRD approach enables the predictive determination of the best reaction concept considering highly innovative process intensification options. Thereby, this method provides a key stone for the development of more economical and more sustainable chemical reactors and processes of the future.
CRIS-Team Scopus Importer:2019-10-08